Muscular strength is associated with self-esteem in college men but not women. (December 2016) - Ciccolo, Joseph T; SantaBarbara, Nicholas J; Dunsiger, Shira I; Busch, Andrew M; Bartholomew, John B
Muscular strength is a well-known predictor of morbidity and mortality. Similarly, self-esteem is a predictor of health and well-being. The relationship between these two variables, however, is currently unknown. This study examined the cross-sectional relationship between maximal muscular strength (i.e. handgrip and one-repetition-maximum (1-RM) squat) and global self-esteem in 126 college students. Significant correlations were found between both measures of muscular strength and self-esteem. Further analyses revealed that these relationships were only significant for men. Based on these results, additional research is needed to further explore the relationship between muscular strength and self-esteem, especially in other demographic groups and longitudinally.